'A welcoming refuge?' The experiences of European Jewish refugees in the Dutch East Indies, set against other Asian destinations, 1933-1965. Issue 2 (3rd April 2021) - Rosen Jacobson, Liesbeth
ABSTRACT: Historians have often studied European Jews in connection with the Second World War. However, their experiences as refugees in Asian colonies are less examined. In this article I examine European Jewish refugees in the Dutch East Indies, with British India, Singapore and Shanghai as counterpoints. The focus is on the way European Jewish refugees were received and how that impacted their identity, as well as the role of international organisations. By using ego documents and articles from local newspapers I assess the meaning of the Dutch East Indies as a place of refuge for European Jewish refugees among other Asian destinations.